The Effectiveness of the Learning Strategy of Thinking Ability Improvement (SPPKB) to Enhance Students’ Higher Order Thinking Skill (HOTS) in Economics Learning at SMA 1 Kawedanan Magetan - Sudarmiani, Sudarmiani (Universitas Malikussaleh, 2020)
The study's purpose was to investigate the effectiveness of Learning Strategy of Thinking Ability Improvement (SPPKB) application used to improve Higher Order Thinking Skills (HOTS) of social study (IPS) students in economics learning. The research method used a quasi-experimental method with pretest-posttest control group design and effectiveness data analysis using a t-test. The research populations were 1-eleventh grade social study class (XI IPS 1) having 25 students as the experimental class and 2-eleventh grade social study (XI IPS 2) class having 27 students as the control class. The different treatment between the two classes was that in the experimental class applied the SPPKB model while the control class employed the conventional learning model. The study results reveal that the use of SPPKB has never been implemented in economics learning in the classroom. The effectiveness of using the SPPKB shows the values of the t-test results for Higher Order Thinking Skills (HOTS) abilities with significance values of 0.000 <0.05. These results indicate that there is a significant influence on the SPPKB implementation to enhance students' Higher Order Thinking Skills (HOTS) in economics learning.